PENYELESAIAN SENGKETA TANAH ADAT SUKU MELAYU DATUK MUDO DI KABUPATEN KAMPAR - FATTIAH NAMIROH; Rika Lestari; Ulfia Hasanah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
Basically, ulayat land is a ulayat right for customary law communities,which according to customary law ulayat rights can only be owned together, usedtogether and used together. ulayat land may not be owned individually, becausebasically ulayat land cannot be sold, given, or pawned to anyone. However, inreality there are cases of selling ulayat land of the Malay Datuk Mudo by thenephew of the Malay tribe of Datuk Mudo. The purpose of writing: first : to findout the regulation regarding the transfer of ulayat rights of the Malay DatukMudo indigenous peoples according to customary law. Second : knowing how toresolve disputes over customary land of the Malay Datuk Mudo tribe according tocustomary law. This type of research can be classified in the type of sociologicalresearch. This research was conducted in Sei Jernih Hamlet, Pasir SialangVillage, Bangkinang District, Kampar Regency. The population and sample arethe parties related to the problems studied by the authors in this study. Collectingdata by interview method and library study.From the results of the research problem there are two main things thatcan be concluded. First: The ownership of customary land rights for the MalayDatuk Mudo indigenous peoples basically cannot be transferred or traded, ormortgaged, which has been explained by ninik mamak based on existingcustomary law regulations or based on national regulations that have been set. bythe Kampar Regency Government. Except based on the conditions and coercion ofthe customary leader through consultation with traditional officials, religiousscholars, and ninik mamak. Second: The dispute resolution carried out in thisstudy has reached the point of deliberation and consensus. In which thisdeliberation was carried out with traditional officials, ninik mamak, religiousscholars, government and the indigenous Malay tribal community, Datuk Mudo.However, the dispute over the customary land of the Datuk Mudo Malay tribe inKampar Regency has not been resolved.Key words: Transfer of ulayat rights- ulayat land